Pengajaran yang Inovatif dapat Meningkatkan Minat Membaca pada Anak Sekolah Dasar - Parulian Sibuea; Najla Mardhiyah Lubis; Syafriyandi Aziz (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
Reading intelligence greatly affects students. The overall responsibility for developing an interest in reading in primary school children should rest with teachers at school, parents at home and students. One of the obstacles is the low interest of primary school students in reading. Because lack of interest in reading can hinder children's growth, development, and learning, it can lead to poor performance in the future. The reason for students' low interest in reading is their own reluctance to read. Teachers also do not require students to read books in class. To increase students' interest in reading in primary grades, it is necessary to maintain their interest in reading and provide them with exposure to reading materials so that they can become accustomed to reading. Having a reading habit from childhood will help develop a strong interest in reading in the future. The purpose of this study is to discuss various innovative teaching methods that can be used to increase children's interest in reading in primary schools. It is important that teachers encourage students' interest in reading in school. Research is conducted by developing research questions and searching for journal references suitable for data analysis. Google Chendikia or Google Scholar is used to search the Internet for a collection of journals. Data is studied, examined and compared with other data. This study uses a quantitative descriptive approach. The analysis found that this could potentially increase students' interest in reading in primary schools.